Towards a people's culture - Staal, Jonas; Sison, Jose Maria (Utrecht BAK, 2013)
"New World Academy (NWA) invites progressive political organizations to share with artists and students their views on the role of art and culture in political struggles. Together, they engage in critical thinking through concrete examples of transformative politics and develop collaborative projects that question and challenge the various frameworks of justice and existing models of representation. NWA proposes new critical alliances between art and progressive politics, as a way to confront the democratic deficit in our current politics economy, and culture." -- Provided by publisher
Foreword Maria Hlavajova -- Introduction Jonas Staal -- Cultural imperialism in the Philippines Jose Maria Sison -- Talks at the Yenan forum on literature and art Mao Tse-tung -- The bladed poem Jose Maria Sison -- Poems and prose, with an introduction by Jose Maria Sison Ericson Acosta -- Interviewed by Jonas Staal I am a cultural worker Ericson Acosta -- Terrorist trials as a stage: some notes on performativity Beatrice de Graaf -- The guerilla is like a poet Jose Maria Sison -- Protest puppetry: an update on the aesthetics and production of effigy-making, 2005-2012 Lisa Ito -- Definition of terms Alice G. Guillermo.
FA-2911g donated by Ma'am Lisa Ito.
Keywords: Art -- Political aspects; Politics in art; Arts and society